An investigation of the effect of pulse electrochemical deposition parameters on morphology, hardness and corrosion behaviour in the marine atmosphere. (2nd December 2019) - Prasannakumar, R. S.; Bhakyaraj, K.; Chukwuike, V. I.; Mohan, S.; Barik, R. C.
ABSTRACT: Corrosion is one of the major problem that we encounter in our society. Engineering the surface properties of metallic materials are very crucial in corrosion protection. Pulse electrochemical deposition with square wave has successfully been applied to deposit copper from acidic vitriol electrolyte. The influence of the pulse parameter and hardness of the electrodeposits were investigated in depth. Based on the analysis of the microstructure the pulsed electrodeposited copper in 3.5% NaCl solution was studied using potentiodynamic polarisation and electrochemical impedance spectroscopy. Nanoindentation, Scanning electron microscopy and X-ray diffraction studies revealed an increase in hardness and microstructural arrangement respectively with duty cycles. An appreciable increase in corrosion resistance was obtained at high duty cycles and optimised average current density, as indicated by gravimetric and electrochemical methods conducted under flow conditions.